Genesis n° 45 (2017), «Hugo» (edited by Jean-Marc Hovasse) (Prassi Ecdotiche della Modernità Letteraria, 2020)
This review is dedicated to «Genesis» 45 (2017). «Genesis» is a six-monthly magazine in French, promoted by the Institut des textes et manuscrits modernes (ITEM) in Paris, the center of studies and reflections on genetic criticism. This number, entitled "Hugo" and edited by Jean-Marc Hovasse, is available online at the following address: https://journals.openedition.org/genesis/1722